The awareness of the anti litter bugs campaign among the employees of Penampang District Council / Nazrie Wahid and Azrul Azizi Adus - Wahid, Nazrie; Adus, Azrul Azizi (2012)
The natural environment is degrading fast, especially in a modern, capital-oriented and fast paced situation that we are currently living in. It is ironic that although we have new technologies that can substitute the usage for most of the natural resources, the environment is still in its worst condition, probably because of litter and the problem of littering. As emphasized by Singhapakdi and LaTour (1991), littering is one of the ancient forms of environmental deterioration. In most cases, litter is the main cause for pollution (Hansmann and Scholz, 2003) and litter would not exist without people, according to Campbell (2007). Keenan (1996) define littering as careless and incorrect disposal a certain amount of wastes. Littering will also leave traces of discarded and unnatural elements in the environment (Green, 2001); hence will pollute the particular area. According to Calver (1959), rubbish will encourage the breeding of pests such as rats, flies and mosquitoes. It will also cause accidents to occur whether directly and indirectly if they were discarded on public places such as on roads, public parks, beaches, lakes, playgrounds and others. Rubbishes that were uncollected will be the source of unexpected accidents such as fires, injuries or even death (Calver, 1959). Litter is now viewed as a serious environmental issue (Wang and Pereira. 1980). It is portrayed as something that is wrongly placed, is bad for the environment, harmful to health and may bring disease.